Knee Joint Radiographic Examination Technique with Anteroposterior and Lateral Projections in Osteoarthritis Cases - Rofiqoh Evi Prastiwi; Bagus Aji Pangestu; Fani Susanto (Proceedings Series on Health & Medical Sciences, 2021)
Radiographic examination of the knee joint in Osteoarthritis (OA) cases was generally performed using anteroposterior (AP), lateral and oblique projections. However, at the Regional General Hospital (RSUD) of Ajibarang, in the case of OA the knee joint only used AP and lateral projections. The purpose of this study was to determine the radiographic examination procedure and ensure the criteria for the image generated from the AP projection and lateral examination of the knee joint in OA cases. This research was a qualitative descriptive with a case study approach. Collecting data on 1 knee joint patient with OA in Ajibarang Hospital using observation, documentation and interviews with radiographers and radiologist. Data analysis used open coding in the form of quotations. The results showed that the AP and lateral projections were performed with the central ray perpendicular to the cassette and showed the distal femur, tibia, proximal fibula and patella, the femoropatellar joint and the knee joint were exposed and the true lateral was shown by superposition of the femoral condyles. Finally, examination of the knee joint of OA cases at Ajibarang Hospital with AP and lateral projections can still display the anatomy of interest and determine the diagnosis of OA cases.